Building agency through participatory video: insights from the experiences of young women participants in India. (2nd September 2017) - Singh, Namita; High, Chris; Lane, Andy; Oreszczyn, Sue
Abstract: Participatory video (PV) is being used by several nongovernment organizations (NGOs) in many different countries. It is often assumed to be a non-problematic process that enables less powerful groups to gain power and participate in social change. While scholars have for long critiqued participatory approaches, it is only in recent years that academic and professional debates that challenge assumptions about PV have emerged. This paper adds to those debates, while focusing primarily on critiquing the PV practice. Drawing on the concepts of participation, agency, and gender, it examines how the agency of less powerful groups can be affected over a period of time as they participate in PV projects initiated by NGOs. It discusses these issues through a case study of a long-term PV project done with young women in a community in Hyderabad (India), undertaken during a doctoral research. It draws attention to the several aspects of a long-term PV project that impact agency-development. The paper argues that while PV can enable participants to gain agency, it is equally challenging to do so in the presence of power relations.